2020
DOI: 10.1093/ajh/hpaa164
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Microcirculation Profiles in the Progression of Hypertension in Spontaneously Hypertensive Rats

Abstract: BACKGROUND Emerging evidence indicates that the pancreas serves as a major source of degrading protease activities and that uncontrolled proteolytic receptor cleavage occurs under hypertensive conditions, which leading to systemic dysfunction and end-organic damage. However, changes in pancreatic microcirculation profiles during the progression of hypertension remain unknown. METHODS Pancreatic microcirculatory blood distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Microcirculation refers to the terminal vascular and lymphatic network of the systemic circulation, which consists of arterioles, capillaries, venules, and lymphatic vessels, and plays a vital role in maintaining the physiological function of tissues. Accumulating data, including ours, have demonstrated that decreased microvascular blood perfusion contributes to the development of essential hypertension through a loss of endothelial nitric oxide synthase (eNOS) activity or reduction in bioavailable NO 4,5 . In lymphatic endothelial cells, eNOS is required for robust lymphatic contractions under physiological conditions, 6 and eNOS can stimulate lymph‐angiogenesis and modulate the activity of afferent and efferent collecting lymphatics, which therefore enable blood pressure to be maintained within normal ranges.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Microcirculation refers to the terminal vascular and lymphatic network of the systemic circulation, which consists of arterioles, capillaries, venules, and lymphatic vessels, and plays a vital role in maintaining the physiological function of tissues. Accumulating data, including ours, have demonstrated that decreased microvascular blood perfusion contributes to the development of essential hypertension through a loss of endothelial nitric oxide synthase (eNOS) activity or reduction in bioavailable NO 4,5 . In lymphatic endothelial cells, eNOS is required for robust lymphatic contractions under physiological conditions, 6 and eNOS can stimulate lymph‐angiogenesis and modulate the activity of afferent and efferent collecting lymphatics, which therefore enable blood pressure to be maintained within normal ranges.…”
Section: Introductionmentioning
confidence: 93%
“…Accumulating data, including ours, have demonstrated that decreased microvascular blood perfusion contributes to the development of essential hypertension through a loss of endothelial nitric oxide synthase (eNOS) activity or reduction in bioavailable NO. 4 , 5 In lymphatic endothelial cells, eNOS is required for robust lymphatic contractions under physiological conditions, 6 and eNOS can stimulate lymph‐angiogenesis and modulate the activity of afferent and efferent collecting lymphatics, which therefore enable blood pressure to be maintained within normal ranges. Nevertheless, even though it is a comprehensive aspect of integrated microcirculation profile, the relationship between lymphatic microcirculation and essential hypertension is not well studied.…”
Section: Introductionmentioning
confidence: 99%
“…The role of signal components mentioned above has been studied fragmentarily in microvasculature oscillatory processes. So, in spontaneously hypertensive rats at the age of 8 to 18 weeks, spectral analysis using wavelet transform revealed a significant decrease in the amplitudes of pancreatic microcirculation oscillations in the endothelial range, which can be partially explained by an increase in plasma levels of nitrite/nitrate, endothelin-1, malonic dialdehyde and interleukin-6 and a decrease in the level of superoxide dismutase in the blood [ 176 ]. A comprehensive study of the spectral characteristics of murine skin micro-hemodynamics oscillations and oscillations of Ca 2+ and NO concentrations in the cytoplasm of cultured murine microvascular endotheliocytes showed the presence of low-frequency oscillations of both Ca 2+ and NO concentrations in the frequency interval coinciding with the interval of NO-independent endothelial activity of skin microcirculation [ 177 ].…”
Section: No-dependent Regulation Of Vasodilation and Its Abnormalitie...mentioning
confidence: 99%